2011
DOI: 10.1007/s10336-011-0667-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying changes in abundance without counting animals: extensions to a method of fitting integrated population models

Abstract: Article (refereed) -postprint AbstractIntegrated population modelling techniques combine information from population surveys and independent demographic studies to estimate population size, survival and productivity rates simultaneously. We review the development of the approach, and investigate further the potential to incorporate sources of population survey data other than those currently employed. Generally, the simpler the field protocol, the more data can be gathered; in the simplest case only a list of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recognizing the interest in combining capture–recapture and occupancy protocols, Freeman & Besbeas () developed an integrated approach in which they combined count survey and ring‐recovery data to estimate abundance. Based on simulations and the analysis of a real case study, they demonstrated that combining different sources of data provided a better precision allowing the detection of change in abundance and other demographic parameters that would not be possible otherwise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the interest in combining capture–recapture and occupancy protocols, Freeman & Besbeas () developed an integrated approach in which they combined count survey and ring‐recovery data to estimate abundance. Based on simulations and the analysis of a real case study, they demonstrated that combining different sources of data provided a better precision allowing the detection of change in abundance and other demographic parameters that would not be possible otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Based on simulations and the analysis of a real case study, they demonstrated that combining different sources of data provided a better precision allowing the detection of change in abundance and other demographic parameters that would not be possible otherwise. Nevertheless, Freeman & Besbeas () assumed that detectability was equal to 1 and did not explicitly consider the observation process.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, a likelihood factor for the demographic data is multiplied by a likelihood factor for the survey data, with some parameters shared with the first factor, to form a joint likelihood. Estimating an integrated population model amounts to optimizing the joint likelihood, which can be computationally demanding for complex sampling schemes (Freeman and Besbeas 2012). A pseudo ML approach to the survey likelihood could simplify analyses substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple data sources are usually combined using joint-likelihood methods (but see Pacifici et al, 2017) and often have the advantage of increased population parameter precision (Besbeas et al, 2002;Schaub & Abadi, 2011). Several data type combinations have been used in these joint models, including capture-recapture, count, and fecundity data (integrated models; i.e., Ahrestani, Saracco, Sauer, Pardieck, & Royle, 2017;Schaub & Abadi, 2011;Wilson, Gil-Weir, Clark, Robertson, & Bidwell, 2016), capture-recapture and census/count data (Catchpole, Freeman, Morgan, & Harris, 1998), radiotelemetry and capture-recapture data (Powell, Conroy, Hines, Nichols, & Krementz, 2000), count and detection/non-detection data (Zipkin et al, 2017), and capture-recapture and detection/ non-detection data (Freeman & Besbeas, 2012). In addition, recent advances with Bayesian hierarchical models have illustrated the utility of integrated data models (Schaub & Abadi, 2011;Schaub et al, 2007), and created opportunities for designing future studies incorporating multiple data sources.…”
Section: Introductionmentioning
confidence: 99%